Observation on void formed in oxide scale of Fe-Cr-Ni alloy at 1073K in dry and humid environments - Akhbar, Kaderi; Ani, Mohd Hanafi; Othman, Raihan; Mohd Zainal, Ahmad Zaki (2011)
Void formation in oxide scale during high temperature oxidation is a common phenomenon.Over a long period of time voids will affect the mechanical property of scales by influencing the cracking and spalling. Voids formed in dry environment are different than that of formed in humid environment. With the presence of water vapor in humid environment the formation of void will increase, thus greater number of void compared to that in dry environment. Fe-Cr-Ni alloy samples were exposed isothermally at 1073 K in air ((POO2=0.21atm = 2.1 × 10 5 Pa) and humid (air + steam) environments. XRD analysis done to all samples confirms that Fe2O3, Fe3O4, NiCr2O4, FeCr2O4, Cr2O3 and NiO phases exist in the scale. EDX analysis done shows varying compositions of Fe,Cr,Ni and O in outer and inner oxide scale, oxide scale/metal interface and metal. Field emission scanning electron microscope (FE-SEM) was used to investigate voids formed in the cross sections of the oxidized samples. Volume fraction of voids in the oxide scale was calculated in accordance to the cross sectional area fraction of voids in the scale. It shows that Fe-Cr-Ni alloy samples exposed in humid environment has as high as 71% more voids than that exposed in dry environment. It is concluded that the humid environment increased the number of void formed in the oxide scale, thus facilitates the exfoliation of protective scale during the oxidation.